2020
DOI: 10.1002/adma.202005431
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Insight in the Interfacial Effect in Ferroelectric Polymer Nanocomposites

Abstract: Recent advances in the assembly of ceramic oxides and ferroelectric polymers to create ferroelectric polymer nanocomposites have provided a fertile new ground for controlling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 59 publications
3
51
0
1
Order By: Relevance
“…Based on the overall data, we can conclude that by increasing the Ag-BT hybrid filler addition in the composites, the formation of the polar structure β and γ phases of PVDF is promoted, although the major phase remains the α-polymorph. An increase of the electroactive β and γ phases of PVDF as induced by the presence of silver inclusions was also reported in recent literature [ 43 , 44 ]. A detailed nanoscale experimental study combined with DFT calculations demonstrated that the mechanism favoring the formation of polar phases resulted from a polar interfacial coupling between the filler and the molecular chains of the polymer promoting specific polar arrangements, i.e., the presence of electroactive phases [ 44 ].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Based on the overall data, we can conclude that by increasing the Ag-BT hybrid filler addition in the composites, the formation of the polar structure β and γ phases of PVDF is promoted, although the major phase remains the α-polymorph. An increase of the electroactive β and γ phases of PVDF as induced by the presence of silver inclusions was also reported in recent literature [ 43 , 44 ]. A detailed nanoscale experimental study combined with DFT calculations demonstrated that the mechanism favoring the formation of polar phases resulted from a polar interfacial coupling between the filler and the molecular chains of the polymer promoting specific polar arrangements, i.e., the presence of electroactive phases [ 44 ].…”
Section: Resultssupporting
confidence: 67%
“…An increase of the electroactive β and γ phases of PVDF as induced by the presence of silver inclusions was also reported in recent literature [43,44]. A detailed nanoscale experimental study combined with DFT calculations demonstrated that the mechanism favoring the formation of polar phases resulted from a polar interfacial coupling between the filler and the molecular chains of the polymer promoting specific polar arrangements, i.e., the presence of electroactive phases [44]. The structural modifications induced by the presence of an inorganic hybrid filler are expected to support a permittivity increase and in general, to enhance ferro-, pyro-, and piezoelectric responses in the flexible composites concerning the characteristics of the pure PVDF material.…”
Section: Phase Composition Analyzed By X-ray Diffraction and Infrared...supporting
confidence: 68%
See 1 more Smart Citation
“…We finally use AFM‐IR to gain deeper structural insights into the field‐induced behavior by PFM. Here we use contact mode [ 44 ] which is the same as PFM but different from the tapping mode used in our previous AFM‐IR measurements. [ 19 ] The advantage of the contact mode in AFM‐IR over the tapping mode is a better signal‐to‐noise (S/N) ratio of local spectra due to the fact that the contact probe is not tapping/hammering the surface of the fixed local area during operation and the signal is amplified by measurement at the contact resonance.…”
Section: Resultsmentioning
confidence: 99%
“…Various ferroelectric systems have been studied over the last decades, ranging from the common perovskite ferroelectrics, such as BaTiO 3 [ 16 , 17 , 18 , 19 ], multiferroic materials [ 20 , 21 ], such as BiFeO 3 [ 22 , 23 , 24 ] and hexagonal manganites [ 25 , 26 ], multilayered structures of different ferroelectrics [ 14 , 27 , 28 ] to ferroelectric polymers [ 29 , 30 , 31 , 32 ]. In the prototypical perovskite ferroelectrics, the spontaneous polarization originates from the off-center displacement of the transition metal cation at the center of the oxygen octahedron.…”
Section: Introductionmentioning
confidence: 99%